2015
DOI: 10.1192/s2056474000000246
|View full text |Cite
|
Sign up to set email alerts
|

Implications of participatory methods to address mental health needs associated with climate change: ‘photovoice’ in Nepal

Abstract: ‘Photovoice’, a community-based participatory research methodology, uses images as a tool to deconstruct problems by posing meaningful questions in a community to find actionable solutions. This community-enhancing technique was used to elicit experiences of climate change among women in rural Nepal. The current analysis employs mixed methods to explore the subjective mental health experience of participating in a 4- to 5-day photovoice process focused on climate change. A secondary objective of this work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Social and environmental factors that may protect mental health and wellbeing were highlighted, including being on the land and connecting to Inuit culture, as well as how Inuit-led monitoring of environmental conditions can guide climate change adaptation that considers intangible losses and damages to well-being and ways of living [ 92 , 93 , 94 ]. A study from Nepal revealed similar themes [ 95 ], while a 15-year prospective cohort study of Hurricane Katrina survivors (New Orleans, LA, USA) has concluded that mitigation efforts should prevent trauma exposure through investments in climate resilience and eliminating evacuation impediments [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Social and environmental factors that may protect mental health and wellbeing were highlighted, including being on the land and connecting to Inuit culture, as well as how Inuit-led monitoring of environmental conditions can guide climate change adaptation that considers intangible losses and damages to well-being and ways of living [ 92 , 93 , 94 ]. A study from Nepal revealed similar themes [ 95 ], while a 15-year prospective cohort study of Hurricane Katrina survivors (New Orleans, LA, USA) has concluded that mitigation efforts should prevent trauma exposure through investments in climate resilience and eliminating evacuation impediments [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…PhotoVoice has been used for diverse topics in global health (Catalani & Minkler, 2010) and to reduce self-stigma among persons with mental illness in a high-income country (HIC) (Russinova et al, 2014). In Nepal, PhotoVoice was used to address psychological distress associated with climate change among rural women (MacFarlane, Shakya, Berry, & Kohrt, 2015). In RESHAPE, the PhotoVoice topics included introduction to mental health stigma, writing recovery stories, group norms and training in using camera and photography, confidentiality and ethics, understanding narratives and myth busting to reduce stigma, and learning creative ways of personal story telling through photography.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies highlight the diversity of community adaptation and resilience strategies used by communities to respond to and understand community perspectives of climate change and its associated threats (Hissa 2016;Bulla and Steelman 2016). For instance, Photovoice has been used to examine marine conservation and climate change in coastal communities on the Coast of Thailand and with women in rural Nepal to record experiences of climate change and mental health needs (Bennett and Dearden 2013;MacFarlane et al 2015). The Photovoice method assisted women in the Nepal study to identify local and existing resources, develop adaptive strategies, and promote mental health in relation to climate change (MacFarlane et al 2015).…”
Section: Global Photovoice Literaturementioning
confidence: 99%
“…The research's broader implications advance our understanding of community views of climate change that Baldwin and Chandler (2010) state is "an emerging and critical area of international [climate change] research" (Baldwin and Chandler 2010). The Photovoice method was also utilized within an Ontario community to understand their perceptions on disaster recovery and climate-related threats related to a recent F3 tornado and with farmers in North Carolina concerning vulnerability to climate change (Bennett and Dearden 2013;MacFarlane et al 2015;Baldwin and Chandler 2010;Hissa 2016;Bulla and Steelman 2016). Findings from farmers in North Carolina suggest that developing active social networks and employing new adaptive behaviors may increase small farm resilience to climate change threats (Bulla and Steelman 2016).…”
Section: Global Photovoice Literaturementioning
confidence: 99%